Back Cover: Bicyclic β‐Sheet Mimetics that Target the Transcriptional Coactivator β‐Catenin and Inhibit Wnt Signaling (Angew. Chem. Int. Ed. 25/2021). Issue 25 (19th April 2021) - Wendt, Mathias; Bellavita, Rosa; Gerber, Alan; Efrém, Nina‐Louisa; van Ramshorst, Thirza; Pearce, Nicholas M.; Davey, Paul R. J.; Everard, Isabel; Vazquez‐Chantada, Mercedes; Chiarparin, Elisabetta; Grieco, Paolo; Hennig, Sven; et al.
Abstract : Bicyclic peptidomimetics bind the transcriptional coactivator β‐catenin. A structure‐based design strategy has been applied to minimize a 52 amino acid binding motif into bicyclic 16‐mer β‐sheet mimetics. The biologically most active mimetic exhibits robust cellular uptake and inhibits Wnt signaling in a cell‐based assay, as reported by Tom N. Grossmann and co‐workers in their Research Article on page 13937 .